2019
DOI: 10.3390/rs11202336
|View full text |Cite
|
Sign up to set email alerts
|

Visible and Near-Infrared Reflectance Spectroscopy Analysis of a Coastal Soil Chronosequence

Abstract: The soil chronosequence is a useful method for investigating pedological theories. Soil chemical, physical and mineralogical properties in chronosequences change over time and exhibit systematic and time-dependent trends, which can be used to analyze the rates and directions of pedogenic changes. The potential of soil spectroscopy as an emerging, rapid and cost-effective technique for predicting soil properties has been widely accepted and has motivated the application of spectroscopic techniques to the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 77 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…Thus, temporal changes in soil properties have been considered by evaluating the ability of spectroscopy to characterize soil chrono-sequence. 55 For example, Awiti et al 56 and Zheng et al 57 concluded that spectroscopy can characterize changes in soil properties after analyzing soil types that corresponded to specific steps of pedogenic processes. Moreover, several studies [58][59][60] quantified soil properties and their degree of alterations during different pedogenic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, temporal changes in soil properties have been considered by evaluating the ability of spectroscopy to characterize soil chrono-sequence. 55 For example, Awiti et al 56 and Zheng et al 57 concluded that spectroscopy can characterize changes in soil properties after analyzing soil types that corresponded to specific steps of pedogenic processes. Moreover, several studies [58][59][60] quantified soil properties and their degree of alterations during different pedogenic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Visible and near infrared reflectance (Vis-NIR) spectroscopy has been widely used to rapidly analyze many properties in various types of soils or sediments [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. As the primary chemical attribute, organic carbon in soils or sediments (SOC) is directly related with Vis-NIR reflectance and has been mainly investigated for 20 years [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies also showed that ASD spectrometers are the most commonly used in the Vis-NIR spectral analysis due to their good performance and reputation [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 17 , 18 , 19 ]. However, ASD spectrometers are expensive, being a barrier to studies on Vis-NIR spectroscopy [ 13 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, when combined with outer product analysis, spectra fusion resulted in improved classification accuracy reaching 68.4%, compared to the SVM data fusion model (61.1%). Another work fused spectral data of eight soil layers collected with a vis-NIR spectrometer for the analysis of a coastal soil chronosequence using 16 soil profiles [16]. A combination of the DUALEM-421S instrument to measure apparent electrical conductivity (ECa) with a traditional soil coring survey and light detection and ranging radar (LiDAR) to measure alleviation and derive terrain attributes was used to measure and map the depth of a peat soil based on a multiple linear regression analysis [17].…”
mentioning
confidence: 99%
“…This is due to the low number of papers submitted, with three of the accepted papers having an indirect link to the topic of the Special Issue. Even when papers linked closely with the project topic, the fusion was sometimes implemented on data collected from the same sensor over time [10,12], space [16], or using different measurement modes [14]. However, the topic holds great potential for application in different domains in soil science, environment, and agriculture.…”
mentioning
confidence: 99%